The Complement Structure of Arabic in Al-Jurumiyyah Book - Khaerul Umam, Siti Lathifatussa’diyyah (Arabic Letters and Department, 2020)
This study aims to describe the complementary structure of Arabic in Al-Jurumiyyah book. A complement is a complementary form in a sentence which holds a function and role as an adverb (adverb function). This study was designed with a qualitative descriptive research model. The data collection method uses the observation method with note-taking technique. Researchers recorded examples of sentences containing complements. Furthermore, data analysis was carried out using distributional method (agih method), in which the researcher examined aspects of language without paying attention to the context of its use. The technique used in data analysis is Bagi Unsur Langsung (BUL) or ‘Immediate Constituent Analysis’ technique by paying attention to the lingual element which is the complement category in Arabic. Furthermore, the researcher used markah (bookmark) reading technique to determine the constituents of complementary fillers in Arabic. The results showed that in Al-Jurumiyyah book there was a complete discussion of the complement structure, namely genetic complement, accusative complement, and dependent complement. Accusative complement includes maf’ûl-muthlaq, maf’ûl li ajlih atau maf’ûl lahu, maf’ûl fîh, maf’ûl ma’ah, a’t-tamyîz, al-châl, al-ististnâ’. Genitive complement in Arabic is represented by a word that is preceded by charf jar particle preposition or in idhâfah form.